Global Frankenstein (Studies in Global Science Fiction,, 2018)
Consisting of sixteen original essays by experts in the field, including leading and lesser-known international scholars, Global Frankenstein considers the tremendous adaptability and rich afterlives of Mary Shelley's iconic novel, Frankenstein, at its bicentenary, in such fields and disciplines as digital technology, film, theatre, dance, medicine, book illustration, science fiction, comic books, science, and performance art. This ground-breaking, celebratory volume, edited by two established Gothic Studies scholars, reassesses Frankenstein's global impact for the twenty-first century across a myriad of cultures and nations, from Japan, Mexico, and Turkey, to Britain, Iraq, Europe, and North America. Offering compelling critical dissections of reincarnations of Frankenstein, a generically hybrid novel described by its early reviewers as a "bold," "bizarre," and "impious" production by a writer "with no common powers of mind", this collection interrogates its sustained relevance over two centuries during which it has engaged with such issues as mortality, global capitalism, gender, race, embodiment, neoliberalism, disability, technology, and the role of science. .